2018
DOI: 10.1038/s41388-018-0226-z
|View full text |Cite
|
Sign up to set email alerts
|

Capillary morphogenesis gene 2 maintains gastric cancer stem-like cell phenotype by activating a Wnt/β-catenin pathway

Abstract: A growing body of evidence shows that the development and progression of gastric cancer (GC) is mainly associated to the presence of gastric cancer stem-like cells (GCSLCs). However, it is unclear how GCSLC population is maintained. This study aimed to explore the role of capillary morphogenesis gene 2 (CMG2) in GCSLC maintenance and the relevance to GC progression. We found that CMG2 was highly expressed in GC tissues and the expression levels were associated with the invasion depth and lymph node metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…GC stem-like cells have been suggested to accelerate the refractory properties of GC, with uncontrolled self-renewal, and tumor-initiating abilities [5]. A growing body of studies have intended to delineate the regulatory mechanisms in GC stemlike cells and to identify strategies targeting GC stem-like cells, in an attempt to curtail the metastasis and recurrence of GC [6,7]. Accumulating evidence has identified molecular pathways, such as cell growth, apoptosis, angiogenesis, and invasion, for potential molecular therapeutic targets for the treatment of GC [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…GC stem-like cells have been suggested to accelerate the refractory properties of GC, with uncontrolled self-renewal, and tumor-initiating abilities [5]. A growing body of studies have intended to delineate the regulatory mechanisms in GC stemlike cells and to identify strategies targeting GC stem-like cells, in an attempt to curtail the metastasis and recurrence of GC [6,7]. Accumulating evidence has identified molecular pathways, such as cell growth, apoptosis, angiogenesis, and invasion, for potential molecular therapeutic targets for the treatment of GC [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among those differentially expressed gene coregulated by EGFR and PKM2, FOSL1, and ANTXR2 are recently suspected to promote cancer progression ( 38 , 39 ). Western blot analysis showed that FOSL1 and ANTXR2 protein levels are downregulated in EGFR- or PKM2-silenced NPC cells ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Some proteins (DKK2 (Dickkopf-related protein 2), DACT1, CDH11, GECG, PKM2, EZH2, CD44v6, MYC, and TERT), microRNAs (miR-1246, miR-9, miR-92a, miR-544a, and miR-483-5p), and long noncoding RNAs (lncR-β-catm and lncR-TCF7) regulate the activation of the Wnt/β-catenin pathway in CSCs prostate CSCs. 141 Capillary morphogenesis gene 2 increases the expression of nuclear β-catenin to regulate the self-renewal and tumorigenicity of gastric CSCs, 151 and SMYD3, which is located downstream of the Wnt pathway, has a similar effect. 152 In addition, long noncoding RNAs and microRNAs also promote selfrenewal of CSCs through the Wnt signaling pathway.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%